VD_FINDINFO Arrêt / 2024 / 772 vom 26. August 2024 - VD Tribunal cantonal (2024)
AIASSURANCE, RENTE D'INVALIDITÉ, ADMISSION DE LA DEMANDE | 28 al. 1 LAI, 28 al. 2 LAI, 4 al. 1 LAI, 16 LPGA, 6 LPGA, 7 LPGA, 8 LPGA, 49 RAI